Maternal And Fetal Outcome Following Severe Anaemia In Pregnancy: Results From Nobel Medical College Teaching Hospital, Biratnagar, Nepal. - Ghimire, Ram Hari; Ghimire, Sita (Journal of Nobel Medical College, 2013)
Background: anaemia is a major contributor to maternal death in developing countries. Since it reduces resistance to blood loss, death may occur from bleeding associated with normal delivery. Objective: To explore the association between anaemia and maternal and perinatal complications. Study Design: Retrospective cohort study. Materials and Methods: 100 pregnant women admitted for delivery and having severe anaemia were studied and compared with 100 non anaemic women matched for age, parity, and gestational age. Adverse outcomes analysed were: pregnancy induced hypertension, Postpartum haemorrhage hypertension, Abruptio Placenta,, Infection, Maternal Mortality, Low Birth Weight, and Perinatal mortality. Results : Compared to nonexposed women, exposed women had an increased risk of pregnancy induced hypertension with odds ratio of 5.06 . Postpartum haemorrhage, incidence of wound infection,Intermediate care unit admission were statistically significant in exposed group .However there was no significant difference in maternal mortality among study group.APGAR score <7 in 5 minutes was 18%in exposed group and 5% in non exposed group (p=0.0039). Intrauterine fetal death was 6% in cases and none of respondants from control group had Intrauterine fetal death (p=0.0128). Frequency of low birth weight was 22% in exposed group and 9% in non exposed group(p=0.011). Conclusions: The burden of anemia in pregnant population is still high in eastern region of Nepal. Severe anemia in pregnancy carries significant risk to mother and fetus. Hence preventive measures need to be implemented at community level. Public awareness regarding pre-pregnancy hemoglobin status and importance of antenatal checkup relating with maternal and fetal adverse pregnancy outcome should be initiated. Journal of Nobel Medical College Vol. 2, No.1 Issue 3 Nov.-April 2013 Page 22-26 DOI: http://dx.doi.org/10.3126/jonmc.v2i1.7668